(u-3)(u+5)=0

Simple and best practice solution for (u-3)(u+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u-3)(u+5)=0 equation:


Simplifying
(u + -3)(u + 5) = 0

Reorder the terms:
(-3 + u)(u + 5) = 0

Reorder the terms:
(-3 + u)(5 + u) = 0

Multiply (-3 + u) * (5 + u)
(-3(5 + u) + u(5 + u)) = 0
((5 * -3 + u * -3) + u(5 + u)) = 0
((-15 + -3u) + u(5 + u)) = 0
(-15 + -3u + (5 * u + u * u)) = 0
(-15 + -3u + (5u + u2)) = 0

Combine like terms: -3u + 5u = 2u
(-15 + 2u + u2) = 0

Solving
-15 + 2u + u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-5 + -1u)(3 + -1u) = 0

Subproblem 1

Set the factor '(-5 + -1u)' equal to zero and attempt to solve: Simplifying -5 + -1u = 0 Solving -5 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1u = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1u = 0 + 5 -1u = 0 + 5 Combine like terms: 0 + 5 = 5 -1u = 5 Divide each side by '-1'. u = -5 Simplifying u = -5

Subproblem 2

Set the factor '(3 + -1u)' equal to zero and attempt to solve: Simplifying 3 + -1u = 0 Solving 3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1u = 0 + -3 -1u = 0 + -3 Combine like terms: 0 + -3 = -3 -1u = -3 Divide each side by '-1'. u = 3 Simplifying u = 3

Solution

u = {-5, 3}

See similar equations:

| -29+12x=29+9x | | 28562=x | | -12+(-4+9)= | | 3(t+7)=7t-3 | | (x^2+7x+10)(x^2+7x+10)(x^2+7x+10)=0 | | -x=-y+2 | | 18=2(3k+1)-4 | | 4x+48=12x | | x^2+10=154 | | 2.5x+6=60 | | 2y^2+3y-35= | | 8y=33-5y | | 9d-9=18 | | 9u=4u+35 | | 6m+4m-m+5=23 | | 6(x+3)-20=32 | | 3x-5x+1=8-2x | | 2x+3+0.75= | | 9y^2+18y+8= | | x^2-16x-132=0 | | 10=30(20)+b | | y=ln(x+2)-4 | | 10(x-2)+12(x+4)=x | | 9x-37=12x+23 | | -7y-2x=-13 | | 5.5x+1.2-0.3=7.2x-3 | | 13=4x?9 | | 12+x^2=8y-y^2 | | -2[3+4(x-1)]=x | | x+2x+3x=306 | | -3-66x=9 | | 5.2x=3x |

Equations solver categories